1972
DOI: 10.1111/j.1751-1097.1972.tb06258.x
|View full text |Cite
|
Sign up to set email alerts
|

Esr Studies of the Low Temperature Irradiation of Keratin and Its Component Amino Acids

Abstract: Abstract— The photoejection of electrons from the aromatic amino acids at 77°K by 290–340 nm radiation was found to involve both monophotonic and biphotonic processes. However, only monophotonic processes are involved when electrons are photoejected from cystine or cysteine. These electrons prefer to attach themselves to adjacent sulphur groups rather than the dielectric traps in the matrix, so that both anionic and cationic radicals are formed. In keratin at 77°K, the disulphide anion radicals are produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The results verified the effect of UV/ozone exposure on decreasing the strength of the irradiated samples and hence their ability to pass air through its structure that is, increasing their air permeability values (Pailthorpe & Nicholls, 1972). The nature of increased air permeability via the UV/ozone treatment of wool fabric samples is related to surface oxidation creating polar groups and modifying or volatilizing surface lipids .Also, previous studies showed that UV/ozone causes photo-oxidation that mainly modifies C 21 fatty acid components of wool surface lipids and oxidizes disulphide (Hawkyard et al, 1997).…”
Section: The Effect Of Uv/ozone On Air Permeability Values Of Tested supporting
confidence: 73%
“…The results verified the effect of UV/ozone exposure on decreasing the strength of the irradiated samples and hence their ability to pass air through its structure that is, increasing their air permeability values (Pailthorpe & Nicholls, 1972). The nature of increased air permeability via the UV/ozone treatment of wool fabric samples is related to surface oxidation creating polar groups and modifying or volatilizing surface lipids .Also, previous studies showed that UV/ozone causes photo-oxidation that mainly modifies C 21 fatty acid components of wool surface lipids and oxidizes disulphide (Hawkyard et al, 1997).…”
Section: The Effect Of Uv/ozone On Air Permeability Values Of Tested supporting
confidence: 73%
“…A great deal of research about UV irradiation of wool involved mainly its 'negative' effects in terms of photoyellowing and photodegradation [6][7][8][9]. Recently, the beneficial effects of UV irradiation have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cystine is a quenching agent for Tyr; previous research [37] has demonstrated that the quenching mechanism occurs via an electron transfer process with the formation of the radical anion RSSR˙À Although the excited Trp undergoes intersystem crossing to triplet states, studies on wool have suggested that singlet states are quenched more effectively than triplet states [38]. However, there is no evidence of an energy transfer from Trp to cystine in an aqueous system during irradiation [34].…”
Section: Introductionmentioning
confidence: 99%